2010
DOI: 10.1016/j.febslet.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin‐3‐gallate protects motor neurons and regulates glutamate level

Abstract: a b s t r a c tEpigallocatechin-3-gallate (EGCG) is a major component of green tea polyphenols which displays potential properties of anticancer and neuroprotection. Here we show that protection of motor neuron by EGCG is associated with regulating glutamate level in organotypic culture of rat spinal cord. In this model, EGCG blocked glutamate excitotoxicity caused by threohydroxyaspartate, an inhibitor of glutamate transporter. This property of EGCG may be not due to its intrinsic antioxidative activity, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…It is a powerful antioxidant exhibiting multifunctional properties, including anti-inflammatory, anti-apoptosis, neuroprotective effect (Sutherland et al 2006;Zhang et al 2007Zhang et al , 2008Peng et al 2008;Xie et al 2010). Recent researches showed that EGCG also reduced the glutamate excitotoxicity, promoted the viability of neuronal cells by inhibiting ionotropic Ca 2+ influx, reduced the excitotoxin-induced malondialdehyde (MDA) production and decreased the reactive oxygen species level in a dose-dependent manner (Lee et al 2004a,b;Fu & Koo 2006;Fang et al 2010;Yu et al 2010). Besides of that, EGCG was found to regulate the glutamate level by an increase in the glutamate uptake of astrocytes, and the activity of excitatory amino acid transporter 2 (EAAT2), the essential protein for the clearance of synaptically released glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…It is a powerful antioxidant exhibiting multifunctional properties, including anti-inflammatory, anti-apoptosis, neuroprotective effect (Sutherland et al 2006;Zhang et al 2007Zhang et al , 2008Peng et al 2008;Xie et al 2010). Recent researches showed that EGCG also reduced the glutamate excitotoxicity, promoted the viability of neuronal cells by inhibiting ionotropic Ca 2+ influx, reduced the excitotoxin-induced malondialdehyde (MDA) production and decreased the reactive oxygen species level in a dose-dependent manner (Lee et al 2004a,b;Fu & Koo 2006;Fang et al 2010;Yu et al 2010). Besides of that, EGCG was found to regulate the glutamate level by an increase in the glutamate uptake of astrocytes, and the activity of excitatory amino acid transporter 2 (EAAT2), the essential protein for the clearance of synaptically released glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…46 In an organotypic culture of a rat spinal cord model, EGCG has recently been shown to protect motor neurons by blocking the glutamate excitotoxicity caused by threohydroxyaspartate, an inhibitor of glutamate transporter. 55 Nonetheless, more experiments should be performed to clarify the mechanism of action of EGCG. The signaltransduction pathways should be examined in order to determine whether the EGCG effect on the number of the neurons depends on the interaction with a specific receptor or strictly relates to its antioxidant and -apoptotic properties.…”
Section: Discussionmentioning
confidence: 99%
“…Another widely used model to study ALS employs threohydroxyaspartate (THA), an inhibitor of glutamate transport, to induce motor neuron death in cultured rat spinal cord explants. In this model, EGCG protected motor neurons against THA-induced toxicity, which was accompanied by regulation of glutamate levels in the synaptic cleft, and decreased tissue levels of lipid peroxides [39]. …”
Section: Reviewmentioning
confidence: 99%